A Hybrid Organic-Inorganic Layered tio2 Based Nanocomposite for Sunlight Photocatalysis - (:unkn) unknown (ROYAL SOC CHEMISTRY, 2016)
A novel hybrid nanocomposite constituted of single TiO2 nanosheets sandwiched between stearic acid self-assembled monolayers was synthesized and tested in the photodegradation of methylene blue under sunlight. The product showed better photocatalytic performance than anatase under similar conditions, which may be further improved through sensitization with cadmium sulfide.